Epidemiology and Clinical Features of Listeriosis in Gipuzkoa, Spain, 2010–2020 - Vallejo, Pedro; Cilla, Gustavo; López-Olaizola, Maddi; Vicente, Diego; Marimón, José María (Frontiers in Microbiology, 2022)
Background. Listeriosis continues to be one of the most important notifiable foodborne diseases. However, in Spain, there are few data on the molecular epidemiology of Listeria monocytogenes infections in recent years. Aim. To describe clinical aspects and the molecular epidemiology of human listeriosis during an 11-year period (2010-2020) in Gipuzkoa, north of Spain. Methods. A total of 111 isolates all but one from invasive diseases were studied. Serotyping (agglutination and multiplex-PCR) and MLST was performed to all isolates. Antibiotic susceptibility was performed by the broth microdilution method. Results. Average annual incidence of listeriosis in non-pregnancy associated cases was 1.55 per 100,000 population with one-month mortality of 22.2%. In pregnant women, the average incidence was 0.45 cases per 1,000 pregnancies. Twenty-four STs were identified, serotype IVb ST1 (24.3%) being the most frequent followed by I/IIb ST87 (18.9%), that caused two long outbreaks in 2013-2014. A statistical association between ST219 and meningitis was observed. All isolates were ampicillin susceptible as well as susceptible to other antibiotics used in listeriosis treatment. Conclusion. Despite current control measures, listeriosis continue to be an important cause of mortality in the elderly and of prematurity and abortion in pregnant women. Improvements in the control and diagnosis of listeriosis are needed to reduce the impact of this infection on the vulnerable population.